2020
DOI: 10.3390/ijms21249424
|View full text |Cite
|
Sign up to set email alerts
|

Perspective in Alternative Splicing Coupled to Nonsense-Mediated mRNA Decay

Abstract: Alternative splicing (AS) of precursor mRNA (pre-mRNA) is a cellular post-transcriptional process that generates protein isoform diversity. Nonsense-mediated RNA decay (NMD) is an mRNA surveillance pathway that recognizes and selectively degrades transcripts containing premature translation-termination codons (PTCs), thereby preventing the production of truncated proteins. Nevertheless, NMD also fine-tunes the gene expression of physiological mRNAs encoding full-length proteins. Interestingly, around one third… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 159 publications
(217 reference statements)
1
51
0
2
Order By: Relevance
“…We found poison exons expressed predominantly in Lin-neg cells. This finding underscores the role of alternatively spliced poison exons as a potential regulator of gene expression during differentiation of hematopoietic stem cells as described by others (García-Moreno and Romão 2020; Lareau et al 2007a; Leclair et al 2020; Jacob and Smith 2017). Overall, our single-cell analysis of bone marrow populations revealed that lineage-negative cells express more diverse splice variants with higher content of novel isoforms.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…We found poison exons expressed predominantly in Lin-neg cells. This finding underscores the role of alternatively spliced poison exons as a potential regulator of gene expression during differentiation of hematopoietic stem cells as described by others (García-Moreno and Romão 2020; Lareau et al 2007a; Leclair et al 2020; Jacob and Smith 2017). Overall, our single-cell analysis of bone marrow populations revealed that lineage-negative cells express more diverse splice variants with higher content of novel isoforms.…”
Section: Discussionsupporting
confidence: 81%
“…Of particular interest, SMG1 is involved in nonsense-mediated mRNA decay (NMD, (Powers et al 2020)) and we have observed an overall increase of intron retention in Lin-neg cells (Figure 3B). This observation led us to investigate the expression of "poison exons" of SRSF genes, defined as ultraconserved regions containing noncoding exons, that, cause NMD when spliced-in (Lareau et al 2007b;Leclair et al 2020;García-Moreno and Romão 2020;Jacob and Smith 2017). Indeed, we found such sequences for SRSF2, 5, 6 and 7 when we entered the coordinates published in (Leclair et al 2020).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…In normal cells, not all of these aberrant RNA variants have the possibility to produce protein isoforms. It was proposed that about 30% of alternatively spliced transcripts in human cells contain premature termination codons that will result in the degradation of the RNA through nonsense-mediated decay [ 134 ]. Moreover, great numbers of these RNA variants are noncoding RNA.…”
Section: Neoantigens Produced By Alternative Splicingmentioning
confidence: 99%